Printed stretchable dielectric sensor grids for pressure monitoring in orthopedics - Martin, Sina; Gugel, Lukas; Schedel, Sophie; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
Scoliosis is a spinal deformity that can be treated with a scoliosis brace that applies pressure to the trunk. The child's body adapts to the applied pressure and the spine is corrected. However, the braces are adjusted periodically or after rapid growth without monitoring the adaptation process. This study proposes to investigate the pressure distribution in the internal padding of the brace in order to adapt the orthosis to the individual needs of the patient in the long term. For this purpose, the implementation of dielectric elastomer sensors is used to detect pressure peaks and valleys on a mutual capacitance sensing grid. Subsequently, direct ink writing is used to print electrode lines, allowing analysis of the flexible electrode grid geometries. The electrodes are characterized and tested under uniaxial strain. Furthermore, by placing the electrodes on the padding of the orthosis, the relative pressure distribution can be assessed. Our results demonstrate the application of dielectric elastomer sensors in orthopedics and explore the effect of different printed geometries. Although absolute values have not been evaluated, characterization of relative pressure differences is sufficient to detect pressure points. By monitoring long-term changes, therapy can be tailored to the body's individual adaptation process.
CRIS-Team Scopus Importer:2024-06-07
Keywords: additive manufacturing; Mutual capacitance; orthopedics; percolation; pressure sensor